DNA-assembled visible nanodandelions with explosive hydrogen-bond breakage achieving uniform intra-tumor distribution (UITD)-guided photothermal therapy. (March 2022) - Zhang, Yongming; Cui, Yanna; Li, Mingwang; Cui, Kai; Li, Ruike; Xie, Wenhui; Liu, Liu; Xiao, Zeyu
Abstract: Photothermal therapy (PTT) has received increasing attention for treating tumors. However, a long-standing challenge in PTT is non-uniform distribution of photothermal agents (PAs) in tumor tissues, resulting in limited therapeutic efficiency. Herein, inspired by dandelions blowing away by the wind, we have designed a DNA-assembled visible GRS-DNA-CuS nanodandelion, which can achieve uniform intra-tumor distribution (UITD) of PAs, thus enhancing the photothermal therapeutic efficiency. GRS-DNA-CuS is featured by the formation of hydrogen bond between the core of single-strand DNA-modified Raman nanoprobes (GRS) and the shell of complementary single-strand DNA-modified CuS PAs. Under Raman imaging-guided 1st NIR irradiation, hydrogen bond in GRS-DNA-CuS is explosively broken, resulting in large-sized GRS-DNA-CuS (∼135 nm) be completely dissociated into GRS and ultra-small CuS PAs (∼12 nm) within 1 min. Such an explosive dissociation instantly enhances the local concentration of ultra-small CuS PAs and slightly rises intra-tumor temperature, thus increasing the diffusion coefficient of PAs and promoting their UITD. This UITD of CuS PAs enhances the photothermal anti-tumor effects. Three out of five tumors are completely eliminated under photoacoustic imaging-guided 2nd NIR irradiation. Overall, this study provides one UITD-guided PTT strategy for highly effective tumor treatment by exerting explosive breakage property of hydrogen bond, broadening the application scope of DNA-assembly technique in oncology field.